Protecting fisheries resources and marine ecosystem from climate change: Solutions and legal constraints - Indriyani Rachma; Kumar Singh Manish; Ngoc Trang Vu Thi (BIO Web of Conferences)
Warming, acidification and deoxygenation of the ocean are already affecting the productivity and stability of marine ecosystems. It is projected also that climate change will force the fish stocks that cross through two or more exclusive economic zones to shift significantly from their historical habitats and migration that may lead to international conflict on the transboundary fish stocks. Meanwhile, overfishing and habitat destruction has had long-term effect on marine environment. Recently, the 2023 UNGA Resolution on sustainable fisheries reported the decline in global fish stocks. The resolution called upon the States to identify the impacts on fisheries due to climate change, thus it is crucial for States to consider effective adaptation and strategies to tackle the challenges. The present study is designed to analyse the impacts of climate change on fish and their interdependent ecosystems, but also impacts upon the laws and policies relevant to their exploitation and conservation. By using a comparative approach between three vulnerable countries to climate change, the paper highlights how Indonesia, India, and Vietnam are working to cope with the issues arising from climate change on the fisheries sector. The finding shows how the three countries must modernize their legal frameworks for fisheries management to reflect the current challenges such as climate change and ecosystem-based management.